DYSTOCIA DUE TO DICEPHALIC MONSTER IN A COW - SINGH, GYAN; KUMAR, AMIT (The Indian Journal of Animal Reproduction, 2020)
A case of successful per-vaginal delivery of a dicephalus monster foetus is reported in cow.
Keywords: Cow; Dystocia; Dicephalus; Epidosin; Monster